2020
DOI: 10.3390/app10124277
|View full text |Cite
|
Sign up to set email alerts
|

Whole Organ Engineering: Approaches, Challenges, and Future Directions

Abstract: End-stage organ failure remains a leading cause of morbidity and mortality across the globe. The only curative treatment option currently available for patients diagnosed with end-stage organ failure is organ transplantation. However, due to a critical shortage of organs, only a fraction of these patients are able to receive a viable organ transplantation. Those patients fortunate enough to receive a transplant must then be subjected to a lifelong regimen of immunosuppressant drugs. The concept of whole organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 184 publications
0
20
0
Order By: Relevance
“…These figures have been reproduced with permission from the American Chemical Society [117]. 10 Advances in Polymer Technology process is finalized. Low concentrations (<0.5%) of COS showed prolonged viability of human umbilical cord mesenchymal stem cells and potential wound healing capabilities with no inflammation response and maturation of granulation tissue.…”
Section: Oligosaccharide-derived Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…These figures have been reproduced with permission from the American Chemical Society [117]. 10 Advances in Polymer Technology process is finalized. Low concentrations (<0.5%) of COS showed prolonged viability of human umbilical cord mesenchymal stem cells and potential wound healing capabilities with no inflammation response and maturation of granulation tissue.…”
Section: Oligosaccharide-derived Polymersmentioning
confidence: 99%
“…However, TE is now reaching a new level of complexity: two-dimensional cell monolayers are moving to three-dimensional constructs (or even to four-dimensional ones) [131][132][133]. Cell lines are being replaced by pluripotent and patient-derived cells [134][135][136], and tissue grafts are evolving to organoids and whole organs [10,16,47,[136][137][138][139][140][141]. As such, the materials employed must improve accordingly.…”
Section: Sbps For Tissue Engineering (Te)mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the surrounding environment is important, and 3D cell deposition is necessitated. Tissue engineering technology enables the fabrication of various types of engineered organs such as the pancreas, liver, kidney, ovary, bladder, cornea, muscle, skin, vessel, esophagus, and the like using SCs and biomaterials (Figure 2) [127][128][129][130][131][132][133][134][135][136][137]. Although numerous hurdles (i.e., low cell survival, immune response, and insufficient functions) remain to be overcome, many studies have revealed the effectiveness of engineered tissue transplantation as a novel regeneration method [138,139].…”
Section: D Bioprinting Using Ecm-based Bioinksmentioning
confidence: 99%
“…Although numerous hurdles (i.e., low cell survival, immune response, and insufficient functions) remain to be overcome, many studies have revealed the effectiveness of engineered tissue transplantation as a novel regeneration method [138,139]. Some simple tissues (i.e., artificial epidermis) that are relatively easier to engineer, as well as some vital organs that are in high demand for transplantation, have been developed and are progressing favorably [66,127]. Furthermore, to achieve highly precise engineered tissues, novel biofabrication methods such as 3D bioprinting are being developed actively [140][141][142].…”
Section: D Bioprinting Using Ecm-based Bioinksmentioning
confidence: 99%